Analisis Produktivitas Untuk Meningkatkan Hasil Produksi dengan Menggunakan Metode Objective Matrix (Omax) (Studi Kasus : CV Bakso Empal Sapi) - Gustarico, Akbar; Putri, Erni Puspanantasari (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
CV. Bakso Empal Sapi is a company engaged in the manufacturing sector whose main work is in the form of operational production of finished food in the form of meatballs, the absence of productivity measurements in the company systematically makes it unable to meet production targets or maximize production capacity. Therefore, CV. Bakso Empal Sapi seeks to improve its productivity by measuring each productivity criteria. The method used to make measurements is the Objective Matrix (OMAX) method and weighting using the Likert Scale, then after obtaining the results of the calculation, an evaluation is carried out and find out the root of the problem that occurs against the worst productivity criteria using the Fishbone Diagram. Then an improvement plan is carried out which aims to increase productivity again. From the results of productivity measurements using the OMAX method, it can be seen that the best productivity occurred in December at 741.45 and for the worst productivity occurred in January at 143.38. Then from the achievement of the score it is known that the criteria that contribute less to the productivity index are criteria 5 with a score of 13 and 2 with a score of 21 and a strategy to increase productivity is to evaluate the root causes of decreased productivity in criteria 5 and criteria 2.